2022
DOI: 10.1124/jpet.122.001423
|View full text |Cite
|
Sign up to set email alerts
|

The Novel, Clinical-Stage Soluble Guanylate Cyclase Activator BI 685509 Protects from Disease Progression in Models of Renal Injury and Disease

Abstract: Activation of soluble guanylate cyclase (sGC) to restore cyclic guanosine monophosphate (cGMP) and improve functionality of nitric oxide (NO) pathways impaired by oxidative stress is a potential treatment for diabetic and chronic kidney disease. We report the pharmacology of BI 685509, a novel, orally active small molecule sGC activator with disease modifying potential. BI 685509 and human sGC α1/β1 heterodimer containing a reduced heme group, produced concentration-dependent increases in cGMP that were elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…We have previously shown that sGC activator monotherapy inhibits the progression of diabetic nephropathy in ZSF1 rats, a disease also characterized by oxidative stress (Boustany-Kari et al, 2016). Additionally, BI 685509 has been shown to be a potent activator of heme-free sGC and to demonstrate a low nM potency for the activation of the human and mammalian sGC α1β1 heterodimer (Reinhart et al, 2022). This was contrasted against the sGC stimulator praliciguat (Tobin et al, 2018), which had no effect on heme-free sGC activity (Reinhart et al, 2022).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We have previously shown that sGC activator monotherapy inhibits the progression of diabetic nephropathy in ZSF1 rats, a disease also characterized by oxidative stress (Boustany-Kari et al, 2016). Additionally, BI 685509 has been shown to be a potent activator of heme-free sGC and to demonstrate a low nM potency for the activation of the human and mammalian sGC α1β1 heterodimer (Reinhart et al, 2022). This was contrasted against the sGC stimulator praliciguat (Tobin et al, 2018), which had no effect on heme-free sGC activity (Reinhart et al, 2022).…”
Section: Discussionmentioning
confidence: 97%
“…The small molecule BI 685509 is a potent, NO-independent sGC activator (Reinhart et al, 2022) shown to be well tolerated in Phase I studies in patients with portal hypertension in compensated cirrhosis (Lawitz et al, 2021) and with chronic kidney disease (Cherney et al, 2021) and has progressed to Phase II trials for CSPH (NCT05161481), chronic kidney disease (NCT04736628), and diabetic kidney disease (NCT04750577). In previous preclinical studies, BI 685509 was shown to be a potent activator of heme-free human sGC and was orally bioavailable with rapid absorption in mouse and rat models (Reinhart et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,24 Targeting the NO-sGC-cGMP axis, therefore, is an area of therapeutic interest, especially because sGC activation is associated with kidney protection in experimental models. 22,24 Our aim was to examine the safety, tolerability, pharmacodynamic (PD), and pharmacokinetic (PK) characteristics of BI 685509-a potent, NO-independent activator of sGC 25 -in patients with DKD. Furthermore, given the strong association between albuminuria lowering and protection against DKD, 26 we also explored the impact of BI 685509 on urinary albumin:creatinine ratio (UACR) in the trial cohort.…”
Section: Introductionmentioning
confidence: 99%
“…The most notable commercial success by targeting cGMP metabolism is the development of PDE5 inhibitors such as sildenafil (Viagra), vardenafil (Levitra), and tadalafil (Cialis) to treat erectile dysfunction . cGMP signaling has also been targeted in other disease states including pulmonary hypertension, , retinal disease, diabetes, heart failure, kidney dysfunction, , and neurological disorders. , Due to the importance of cGMP in human health and the need for further drug development, it will be necessary to establish robust and reliable assays to accurately determine cGMP levels.…”
mentioning
confidence: 99%